2018
DOI: 10.1111/jphs.12217
|View full text |Cite
|
Sign up to set email alerts
|

Perception of patients towards the role of pharmacist: a cross-sectional study from selected three hospitals in Central Nepal

Abstract: Objectives To determine the perception of patients towards pharmacist and factors affecting their choice of pharmacy in hospitals of central Nepal. Methods A prospective cross‐sectional study was conducted among outpatients (n = 400) of three different purposively selected hospitals of Bharatpur, Nepal, using a systematic random sampling technique. Information on socio‐demographic features, patient's description about pharmacist, frequency of interaction with pharmacist, reason for interaction, factors affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…A cross-sectional survey in the Sultanate of Oman observed that the participants from the general public had a good level of perception regarding the pharmacist's roles and responsibilities (Jose, Al Shukili, Jimmy, 2015). Also, Shrestha et al found that the overall perception of patients toward the roles and responsibilities of pharmacists was positive (Shrestha et al, 2018). On the other hand, a study in Kuwait indicated that respondents had overall negative perceptions of community pharmacists, moderate expectations of their role, and a slightly positive view of the current pharmacy services (Awad, Al-Rasheedi, Lemay, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey in the Sultanate of Oman observed that the participants from the general public had a good level of perception regarding the pharmacist's roles and responsibilities (Jose, Al Shukili, Jimmy, 2015). Also, Shrestha et al found that the overall perception of patients toward the roles and responsibilities of pharmacists was positive (Shrestha et al, 2018). On the other hand, a study in Kuwait indicated that respondents had overall negative perceptions of community pharmacists, moderate expectations of their role, and a slightly positive view of the current pharmacy services (Awad, Al-Rasheedi, Lemay, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Patients need to perceive the pharmacists positively so that they could provide effective pharmaceutical services to patient. 6 The main factor needed to extend the community pharmacy service is understanding what the public expects and needs from the pharmacy service. Once the knowledge and attitude of the public about community pharmacy services are known, it can assist pharmacists in meeting customers' needs to enhance the service quality that community pharmacists could provide to improve customer satisfaction.…”
Section: Rationale Of Studymentioning
confidence: 99%
“… 5 Patients need to perceive the pharmacists positively so that they can provide effective pharmaceutical services to the patient. 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better understanding of pharmacist's roles and responsibilities is important to enhance pharmacist-patient relationship and patients' satisfaction towards pharmacy services [9]. Previous studies reported varied degree of dissatisfaction towards the services provided by hospital pharmacists, which suggested the need for further quality improvement [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%